2011
DOI: 10.1186/1752-4458-5-24
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the UCLA Child Post traumatic stress disorder-reaction index in Zambia

Abstract: BackgroundSexual violence against children is a major global health and human rights problem. In order to address this issue there needs to be a better understanding of the issue and the consequences. One major challenge in accomplishing this goal has been a lack of validated child mental health assessments in low-resource countries where the prevalence of sexual violence is high. This paper presents results from a validation study of a trauma-focused mental health assessment tool - the UCLA Post-traumatic Str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
96
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(98 citation statements)
references
References 56 publications
2
96
0
Order By: Relevance
“…The PTSD-RI is a commonly used test to help diagnose, treat, and monitor PTSD levels in youth (Murray et al 2011), yielding an Overall Severity score, which at certain levels corresponds to a PTSD diagnosis depending on the population being examined (clinical cut off for single incident trauma victims is 38 and for chronically traumatized children is 31). The three subscales correspond to the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, Text Revision (DSM-IV-TR), PTSD symptom clusters of Re-experiencing, Avoidance, and Overarousal.…”
Section: Methodsmentioning
confidence: 99%
“…The PTSD-RI is a commonly used test to help diagnose, treat, and monitor PTSD levels in youth (Murray et al 2011), yielding an Overall Severity score, which at certain levels corresponds to a PTSD diagnosis depending on the population being examined (clinical cut off for single incident trauma victims is 38 and for chronically traumatized children is 31). The three subscales correspond to the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, Text Revision (DSM-IV-TR), PTSD symptom clusters of Re-experiencing, Avoidance, and Overarousal.…”
Section: Methodsmentioning
confidence: 99%
“…However, important questions remain regarding the best approach to train non specialist healthcare workers to provide mental health services. Additionally, best practice for mental health training are still under-evaluated, as compared, for example, to guidance provided for task sharing in HIV/AIDS care (Murray et al, 2011; Perez-Sales, Fernandez-Liria, Baingana, & Ventevogel, 2011; WHO, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Murray and colleagues (2011) argue that existing guidelines are overly broad and limit replication efforts. Lack of adequate evidence results in brief, one time training approaches and a limited participatory framework.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 We have conducted studies in Zambia to understand local mental and behavioral health problems, validate mental and behavioral assessment instruments, and examine the cross-cultural feasibility of evidence-based treatment. [11][12][13][14][15] These studies culminated in the randomized clinical trial reported in this article, which tests the effectiveness of trauma-focused cognitive behavioral therapy (TF-CBT; http://tfcbt.musc.edu/) 16 for OVC compared with treatment as usual (TAU) provided by lay counselors without previous mental health care training. This trial was a collaboration with Serenity Harm Reduction Programme Zambia, a local nongovernmental organization.…”
mentioning
confidence: 99%